The taxonomic status of grass snake, Natrix natrix (Linnaeus, 1758 (Squamata: Colubridae), with designation of a neotype - Norén, Michael; Åhlander, Erik (Zootaxa, 2020)
As part of an investigation into the status of the near threatened Gotland grass snake, Natrix natrix gotlandica Nilson & Andrén, 1981, endemic to the island of Gotland, we discovered that Linnaeus’ type series of the common grass snake, Natrix natrix (Linnaeus, 1758), is comprised of specimens from three different currently recognized species. To stabilize the usage of the name Coluber natrix, we investigate Linnaeus’ type series, and a specimen which Linnaeus in 1741 examined west of the Swedish city of Nyköping is designated lectotype. The lectotype has since been lost, and a newly collected specimen from the same locality is designated neotype for Coluber natrix. The neotype is deposited in the herpetology collection of the Swedish Museum of Natural History in Stockholm, Sweden, catalog number NRM 8260.